A Short Period of Darkness after Mixing of Growing Pigs Intended for PDO Hams Production Reduces Skin Lesions - Marinelli, Lieta (Animals (Basel), 2020)
SIMPLE SUMMARY: Mixing unacquainted growing pigs is a common practice in commercial herds to adjust the group size to the pen dimensions and to balance the body weights of pigs within pens. Aggressive behavior following regrouping may include fights that can result in skin lesions and detrimental economic effects. Strategies aimed at limiting such issues can therefore improve animal welfare in practice. In the present study, we investigated the effects of darkness, maintained for 48 h after the formation of new social groups, on the expression of agonistic behavior and on the accumulation of skin lesions of growing pigs. The provision of 48 h of darkness significantly reduced the number of skin lesions on the mid- and rear thirds of pigs’ body. However, no corresponding reduction was observed in agonistic behavior, suggesting that darkness decreases the efficacy of aggressions, rather than how often or for how long they are expressed. Furthermore, an analysis of the location of lesions indicates that aggressions towards a fleeing companion, rather than reciprocal ones, were those mostly affected by darkness. The present results identify in the provision of darkness an easily applicable and relatively inexpensive intervention, that leads to the reduction of one of the most problematic consequences of agonistic interactions, i.e., skin lesions. ABSTRACT: Agonistic behavior after the regrouping of unfamiliar pigs has been recognized as one of the major welfare issues for pig husbandry, as it may result in lesions, lameness, and health problems. One scarcely investigated strategy to curb agonistic behavior is reducing the availability of visual stimuli potentially eliciting aggressions. In this study, we investigated the expression of agonistic behavior by growing pigs and the resulting accumulation of skin lesions over a period of 14 days following the formation of new social groups, which occurred in a condition of darkness maintained for 48 h. Compared to a simulated natural photoperiod (12 h light/day), darkness significantly reduced the number of skin lesions on the mid- and rear thirds of pigs’ body (p ≤ 0.01). A lack of corresponding decrease in frequency and duration of agonistic interactions suggests that darkness acts by decreasing the efficacy, not the expression, of aggressions. Furthermore, the location of lesions mostly affected by darkness indicates that the latter mostly acted by reducing the possibility of pigs to convey damage to a fleeing conspecific, rather than to one involved in a reciprocal fighting. The lighting regime provided did not affect growth performance traits of a 17-weeks feeding trial. The present results identify in the provision of darkness an easily applicable, and relatively inexpensive intervention, that leads to the reduction of skin lesions.